Tillage systems affecting rice-wheat cropping system - Qamar, Rafi; ur Rehman, Atique; Javeed, Hafiz Muhammad Rashad; Abdul Rehman,; Safdar, Muhammad Ehsan; Ali, Hasnain; Ahmad, Shakeel (Penerbit Universiti Kebangsaan Malaysia, 2021)
Rice-wheat production is an essential component of cropping systems in the Indus-Ganga Plains (IGP) which play a pivotal role in food security of south Asia. These crops are being cultivated on an area of about 13.5 M ha of South Asia. In rice-wheat cropping system, the major reason for lower wheat grain yield is use of unwise tillage practices during wheat seedbed preparation, cultivation of late maturing rice varieties, water shortage, labor shortage, high cost of fertilizers and poor crop management practices. Resource-conserving technology improves the sustainability and productivity of wheat, which ultimately increase the farmer’s livelihood and reduce poverty. Tillage plays an important role in agricultural operation for soil manipulation to optimize the crop productivity. Different tillage systems are being practiced for wheat production in rice-wheat cropping systems including intensive tillage system, conventional and deep tillage, conservation tillage that consisting of minimum tillage, ridge tillage, and no-till or zero tillage system. Zero tillage gives more accessible and efficient planting system that ensures timely wheat cultivation, cut off the tillage operation, better crop residue management that ultimately minimize the cost of production and keeps environment clean. Operational costs for wheat sowing are 50-60% lower with zero tillage (ZT) sowing than with conventional sowing. The cost saving effect is the main reason for the spread of zero tillage technology in rice-wheat system. Current paper presented a review of different tillage systems and their effects on soil physical properties, plant available water, soil organic matter and nutrients, rice residues, wheat yield and farmer’s economics.